PAIN CHARACTERISTICS ON PATIENT UNDERTAKING HEMODIALYSIS - Afifah, Fatin Hapsah; Nurjannah, Intansari; Sunaryo, Ery Yanuar Akhmad Budi (Belitung Raya Foundation, Indonesia, 2018)
Background: Research in pain especially in patients undertaking hemodialysis is important to be conducted in order to help the process of their hemodialysis therapy. Aim: The aim this study was to describe pain characteristic on hemodialysis patient using Visual Analogue Scale (VAS) and mnemonic PQRST (Provocation, Quality, Regio, Radiation and Time). Methods: This was a descriptive quantitative cross-sectional research. The number of respondents were 72 and they routinely undertook hemodialysis therapy twice a week. The study was conducted in one central hospital in Yogyakarta Indonesia on February to March 2017. Univariate analysis was used to describe respondents’ pain characteristic. Results: The majority of respondents (51.39%) experienced moderate pain, followed by mild pain (33.33%) and severe pain (15.28%). The most painful characteristic in the provocation aspect was movement (87.50%), and the quality of pain was knife-like pain (83.33%). Moreover, hand was the major area of pain (84.72%), and there was no radiation of pain (91.67%). Most of pain was intermittent (97.22%). Of 53% of respondents expressed that the pain had an impact on their lives, specifically in their activities (52.63%), followed by others (15.79%), nausea/vomiting (15.79%), sleep disturbance (13.16%), and appetite (13.16%). However, the pain did not have an impact on their emotion. Conclusion: The respondents experienced mostly moderate pain. The percentage of pain characteristics on PQRST mnemonic was above 80%, and more than half of the respondents experienced moderate pain. Majority of the respondents felt the impacts of the pain in their lives.